Integrating Transformational Leadership And Job Analysis To Optimize Structural Staff Placement: A Systematic Literature Review - kholish atikah Azzam; ansarul fahrudda (LP2IHKI UMSurabaya, 2026)
Abstract Background : Human resource (HR) management in hospitals faces competency mismatches in structural positions and disproportionate workloads. This phenomenon stems from weak organizational needs analysis and flawed bureaucratic structures. Aims : This study aims to provide a novel descriptive theoretical framework on the